Debris Flow Modelling Using RAMMS Model in the Alpine Environment With Focus on the Model Parameters and Main Characteristics - Mikoš, Matjaž; Bezak, Nejc (Frontiers in Earth Science, 2021)
Debris flows are one of the natural hazards that can occur in mountainous areas and endanger people lives and cause large economic damage. Debris flow modelling is needed in multiple applications such as design of protection measures or preparation of the debris flow risk maps. Multiple models are available that can be used for the debris flow modelling and Rapid Mass Movement Simulations (RAMMS) model with its debris flow module (i.e. RAMMS:DEBRIS FLOW) is one of the most frequently used ones. This paper provides a comprehensive review of past debris flow modelling applications in the highland environment with their main characteristics including study location, debris flow magnitude, simulation resolution and Voellmy-fluid friction model parameters ranges (i.e. μ and ξ). Additionally, a short overview of each study is provided. Based on the conducted review it is clear that RAMMS parameter ranges were relatively wide and that model calibration using debris-flow post-event survey field data is the essential step that should be done before application of the model. However, an overview of the parameters can help to limit the parameters ranges in case that one takes into consideration similarity of relevant case studies that were conducted in similar environments if the model should be applied for estimation of debris-flow hazard for potential future events. Most often, the model was used in Europe (i.e. Alpine region). Additionally, the model was used for modelling small and extremely large debris flows.